Arthroscopic treatment of synovial chondromatosis of the shoulder: A case report. Issue 2 (June 2015) - Duymus, Tahir Mutlu; Yucel, Bulent; Mutlu, Serhat; Tuna, Serkan; Mutlu, Harun; Komur, Baran
Abstract Introduction Synovial chondromatosis is a mono-articular arthropathy rarely seen in diarthrodial joints. The classic treatment for synovial chondromatosis is open arthrotomy, synovectomy and complete removal of the free fragments. With recent advances in arthroscopic techniques and methods, the indications for arthroscopic treatment have been extended. Presentation of case A 33-year old female presented with complaints of pain in the right shoulder. On the radiological examination, there were seen to be multiple calcified radio-opaque lesions filling all area of the glenohumeral joint. On computed tomography (CT) examination, again multiple radio-opaque free fragments were determined. Arthroscopy was applied to the right shoulder. The free fragments were completely removed. Approximately 33 free fragments, ranging in size from 0.5 to 1.3 cm, were removed. Discussion Cases of synovial chondromatosis in the shoulder have been rarely reported in literature. Generally the disease is self-limiting. Clinically, symptoms are generally not specific. Restrictions in the joint range of movement occur associated with the mechanical effect of the free fragments and in periods of active use, local pain and swelling may be seen in the shoulder. Simple removal of the free fragments, others have stated that removal with synovectomy is necessary to prevent recurrence of the cartilaginous metaplastic focus. Recurrence rates vary from 0 to 31%. Conclusion Arthroscopic surgery can be successfully applied in the treatment of synovial chondromatosis. The advantages of the method include good visualisation during surgery, low morbidity and early healing.